2020
DOI: 10.1038/s41598-020-69112-w
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol supplementation changes gut microbiota diversity in intact and colorectal cancer-induced ICR male mice

Abstract: The composition of the gut microbiota is influenced by sex hormones and colorectal cancer (CRC). Previously, we reported that 17β-estradiol (E2) inhibits azoxymethane/dextran sulfate sodium (AOM/ DSS)-induced tumorigenesis in male mice. Here, we investigated whether the composition of the gut microbiota is different between male and female, and is regulated by estrogen as a secondary outcome of previous studies. We established four groups of mice based on the sex and estrogen status [ovariectomized (OVX) femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 72 publications
6
47
0
Order By: Relevance
“…However, F/B ratio of zymosan + E2 or zymosan + Laso treated group was similar to the control group. Our study was consistent with other studies showed that estradiol supplementation showed significantly lower level of the F/B ratio compared with control group in a male mouse of colorectal cancer model 26 . E2 treatment increased the relative abundance of Bacteroidetes in leptin-deficient mice 27 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, F/B ratio of zymosan + E2 or zymosan + Laso treated group was similar to the control group. Our study was consistent with other studies showed that estradiol supplementation showed significantly lower level of the F/B ratio compared with control group in a male mouse of colorectal cancer model 26 . E2 treatment increased the relative abundance of Bacteroidetes in leptin-deficient mice 27 .…”
Section: Discussionsupporting
confidence: 93%
“…In male mice of colorectal cancer model, α-diversity, observed OTU count, was increased in E2 supplemented male. And β-diversity was significantly distinguished based on E2 treatment 26 . Fecal microbial diversity was correlated with urinary estrogens in postmenopausal women 29 .…”
Section: Discussionmentioning
confidence: 96%
“…A 2016 study using multiple mouse strains demonstrated that ovariectomy led to microbial dysbiosis although this was impacted by both strain and diet ( 149 ). More specifically, dietary supplementation with the hormone estradiol has been shown to increase microbial diversity in healthy male mice and to impact the ratio of bacteria in the microbiome of a CRC-induced mouse model ( 150 ). The potential protective effect of estrogen was examined in a recent study using the AOM/DSS mouse model of intestinal-specific ERβ deletion and induced colitis and CRC.…”
Section: Sexual Dimorphism and The Tumor Microenvironment In Crcmentioning
confidence: 99%
“…ERb in normal colon epithelia has been experimentally shown to play a role in the prevention of a tumor formation in mouse models, by reducing inflammation of the gut [5]. Furthermore, in-vivo mice-models suggest exogenous estrogens impacting inflammatory markers and reducing proliferation of the crypt [5,6], and changing gut microbiota diversity in CRC-induced males [7]. As this posed link of estrogens with gut inflammation and microbiome might be modifiable, it could contribute to a reduced CRC risk [7], and potentially improved survival.…”
Section: Introductionmentioning
confidence: 99%